МАРКЕТИНГОВИЙ ЗМІСТ МІСЦЕВОЇ ПОДІЇ ЯК ОБ’ЄКТА ФОРМУВАННЯ ТУРИСТИЧНОЇ ПРИВАБЛИВОСТІ ТЕРИТОРІЇ ЗА ДОПОМОГИ ІНСТРУМЕНТІВ СИСТЕМИ МАРКЕТИНГОВИХ КОМУНІКАЦІЙ - Вардеванян, Вардан Альбертович; Vardevanyan, Vardan; Vardevanian, Vardan (Черкаський державний технологічний університет, 2019)
Автор статті досліджує сутність події як маркетингової категорії. Під час дослідження були вивчені конотації події у філософському та культурологічному зрізах. З’ясовано, що подія є результатом особистих переживань споживача. Це суб’єктивне особисте сприйняття дає можливість звичайному випадку вийти за межі побутової пригоди – потрапити на рівень події. Таким чином, подія є штучним утворенням – результатом спільних дій організатора та споживача подій. Цей факт дає змогу розглядати подію як культурний продукт, об’єкт маркетингових зусиль. Описано процес комунікації події на споживача та визначено роль маркетингу у цьому процесі. Доведено необхідність зусиль маркетингу на весь цикл події. Наголошено, що різні форми та види подій дають можливість розширити потенціал цього інструмента у просуванні привабливості території. Зроблено висновок про необхідність вивчення складу контактних та цільових аудиторій, перш за все, для формування цікавого для них контенту інформації про подію та ефективного семантичного ряду інформаційного поля події. In the article, the author investigates the event as a marketing category. During the study, the connotations of the event in philosophical and cultural sections are studied. The general understanding of the event as the result of a special personal perception and evaluation of some actions of the external world is determined. This particular subjective perception allows the ordinary case to go beyond the limits of a domestic incident – to get to the level of the event. Thus, the event is an artificial formation – the result of joint actions of the organizer and the consumer of the event. This fact allows to consider the event as a cultural product, an object of marketing efforts. Marketing actions should be aimed at creating communication between the event and the consumer of the event. These actions should be performed in three time dimensions of the event – before it appears, during the event and for a long time after the event. In addition, emphasis is placed on the need to create special conditions for the event. Since it is possible to talk about the event either in the past or in the future, in the present it is necessary to ensure consumer involvement in the course of the event itself. Organization of communication and preparation of the environment for the occurrence of the event require the marketing to focus on the varieties of events. In the article various approaches to the classification of events have been examined. Understanding of the diversity of events allows to expand its potential in promoting the territory. In addition to understanding the very nature of the event, the article focuses on studying the composition of contact and target audiences of the event. The conclusion is made that the event organizers need to take into account the peculiarities of each of the named audiences in the perception of the event. First of all, this concerns the selection of interesting content for the audience and the formation of an effective semantic series of the event information field. A systematic study of contact and target audiences and communication with them must be carried out in order to prepare acceptable roles for them and to ensure their integration into the event. Only in this way is it possible to turn an ordinary activity into an event
MARKETING CONTENT OF A LOCAL EVENT AS AN OBJECT OF THE FORMATION OF TOURIST ATTRACTION OF THE TERRITORY USING THE TOOLS OF THE MARKETING COMMUNICATION SYSTEM
Keywords: маркетинг подій; івент-маркетинг; подія; місцева подія; маркетингові комунікації; маркетинг територій; споживач подій; marketing of event; event-marketing; event; local event; marketing; communications; marketing of territories; consumer of event